Endophytic Phoma sp. isolated from medicinal plants promote the growth of Zea mays - ASHWINI KEDAR; DNYANESHWAR RATHOD; ALKA YADAV; GAURAVI AGARKAR; MAHENDRA RAI (Smujo International, 2014)
Kedar A, Rathod D, Yadav A, Agarkar G, Rai M. 2014. Endophytic Phoma sp. isolated from medicinal plants promote the growth of Zea mays. Nusantara Bioscience 6: 132-139. Fungal endophytes are reported as rich sources of valuable secondary metabolites and could be used as bio-fertilizers. In the present study, we report growth promotion potential of two Phoma species isolated from Tinospora cordifolia and Calotropis procera on maize. The fungal endophytes enhanced growth in inoculated maize plants compared to non-inoculated plants. The main aim of this work was to assess the growth promotion activity of endophytic Phoma species on maize isolated from T. cordifolia and C. procera.